Elements of reflection on education for sustainable development 30 years after the Bruntland Report - Kostecka, Joanna; Cyrankowska, Maria; Podolak, Agnieszka; Kowalska, Brygida (Studia Ecologiae et Bioethicae, 2019)
The aim of the study was to learn about young people’s judgments on sustainable development and environmental protection depending on their school profile and education. The presentation of their opinions was considered important for assessing the state of sustainable development 30 years after the publication of the Bruntland Report. The perception of the phenomenon of “ecological violence” and the opinions regarding the directions of actions to combat it were also identified. In the authors’ opinion, this concept should be included in the ethical foundations of human behaviour in the 21st century. The research was conducted in 2017 with students of the Faculties of Biology and Agriculture and of Pedagogy at the University of Rzeszow and students of the Faculty of Management at the Rzeszow University of Technology. In order to achieve the study goals, a diagnostic survey using a questionnaire was used. The results indicate that education in sustainable development is not carried out equally in all university institutions. It is often underestimated, although the media clearly emphasise the need to solve current problems in such a way as to minimise the negative effects of sustainability-related decisions made on the economic, social, and ecological dimensions of life. All these dimensions are equally important for the welfare of the human species. The results of the study may indicate the directions of activities necessary in education for sustainable development in the 21st century. In search of effective educational and implementation activities for broadly defined sustainable development, it is also worth presenting, examining, and refining the term “ecological violence”. This article touches on the above issue and is a preliminary consideration in this respect. The authors hope that it will lead them and potential readers to a deeper analysis of the possible meaning of the term “violence” also in relation to environmental resources. The presented research results are regarded as preliminary findings for a deeper analysis of this issue in the future.